Aksesibilitas Anak Tunagrahita di SLB Negeri 01 Bengkulu Selatan - Siregar, Rosi L. Vini; Osira, Yessilia; Meliani, Tesa; Samosir, Fransiska Timoria (Jurnal Ilmiah Widya Sosiopolitika; Vol 6 No 1 (2024): ISU-ISU PEMBANGUNAN, 2024)
Accessibility for children with intellectual disabilities is important when carrying out learning activities at school. The provision of accessible physical and non-physical accessibility will make it easier for children with intellectual disabilities to carry out activities independently. Sekolah Luar Luar is a special educational institution for children with special needs such as children with intellectual disabilities. The purpose of this study is to describe the accessibility of children with intellectual disabilities in SLB Negeri 01 South Bengkulu. This study used qualitative methods and selected informants purposively as many as 10 informants. Data collection techniques use observation, interview, and documentation study techniques. The results showed that the accessibility of children with intellectual disabilities in SLB Negeri 01 South Bengkulu was good when viewed from physical accessibility (facilities and infrastructure). Meanwhile, non-physical accessibility (information, communication, and technology) is still difficult for children with intellectual disabilities to access even though schools have provided whatsaap groups, websites, Instagram, Facebook, and modified the process of delivering material using technology. Accessibility is seen from 4 principles, namely the principles of ease, usability, independence, and safety.